The Effect of Organizational Culture, Work Motivation and Leadership Style on Employee Performance in Tourism Department of Tourism and Culture of City Administration of Central Jakarta - Lailatur Rahmah (INTERNATIONAL PENELITI EKONOMI, SOSIAL, DAN TEKNOLOGI, 2021)
Human resources in institutions/agencies need to be managed professionally in order to achieve a balance between the needs of employees and the demands and capabilities of the organization/agencies. This balance is the main key for institutions/agencies, so that they can develop productively and fairly. Based on the description and explanation regarding the analysis of employee performance as the dependent variable and reviewed through the approach of organizational culture, work motivation and leadership style above, it is an independent variable. Based on the results of the validity test in this study, from 48 statement items on the questionnaire given to employees at the Central Jakarta City Administration Tourism Sub-dept., the overall research results are valid. This is evident from the value of rcountgreater than the value of rtableor r valuecriticalie 0.3.